1999
DOI: 10.1021/jp9909558
|View full text |Cite
|
Sign up to set email alerts
|

Surface Interactions of NH2 Radicals in NH3 Plasmas

Abstract: Using the imaging of radicals interacting with surfaces (IRIS) technique, the scattering of NH 2 on a variety of substrates has been measured during NH 3 , NH 3 /H 2 , and NH 3 /SiH 4 plasma processing. In most cases, NH 2 surface scattering was greater than unity for 300 K substrates, suggesting that NH 2 is produced through surface reactions. Removal of the charged species from the plasma molecular beam results in a significant decrease in scattered NH 2 signal. We have also measured velocity distributions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Thus, changes in the SiF 2 scatter with ion perturbation behave as expected if ion bombardment indeed enhanced desorption of SiF 2 . Similar ion effects have also been observed for CF 2 in a variety of FCPs [39], and for NH 2 in NH 3 plasmas [19,20].…”
Section: Sif 2 Surface Interactions In Sif 4 Plasmassupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, changes in the SiF 2 scatter with ion perturbation behave as expected if ion bombardment indeed enhanced desorption of SiF 2 . Similar ion effects have also been observed for CF 2 in a variety of FCPs [39], and for NH 2 in NH 3 plasmas [19,20].…”
Section: Sif 2 Surface Interactions In Sif 4 Plasmassupporting
confidence: 75%
“…The IRIS experiment allows the study of both the kinetic translational temperature (⌰ T ) and the rotational temperature (⌰ R ) of plasma species with relatively high accuracy [18]. Comparison of ⌰ T for species in the plasma and those scattering off of a substrate provide insight into energy accommodation by surfaces and can also be used to elucidate radical-surface interaction mechanisms [19,20].…”
mentioning
confidence: 99%
“…Also the surface loss of radicals has not been addressed, as no data are available for the surface reactivity of NH and NH 2 on the stainless-steel reactor walls. However, from the data of Fisher and co-workers [19][20][21] it seems that the radicals are not very reactive with the surface. Finally, from the radical densities and NH 3 consumption measured, it can be inferred that a significant amount of the consumed NH 3 flow has to be converted into other stable species in the plasma, such as N 2 and H 2 molecules.…”
Section: -mentioning
confidence: 99%
“…The interaction of NH and NH 2 plasma radicals with the surface of different materials has been addressed by Fisher and co-workers, using a molecular plasma beam in combination with laser-induced fluorescence for radical imaging. [19][20][21] Laser-induced fluorescence has also been used for determining the density of NH and NH 2 produced by NH 3 decomposition on a heated tungsten filament. 22 For depositing systems, few studies of the NH 3 plasma chemistry using mass spectrometry have been reported, for example, for the ammonia-silane chemistry 23,24 and recently also for the ammonia-acetylene chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher and co-workers measured the surface interaction of NH and NH 2 radicals for different types of surfaces using laser induced fluorescence combined with a molecular beam setup. [23][24][25] For N radicals on stainless steel and silicon nitride surfaces, the surface reactivity has been summarized and extended by Kessels et al 17 based on the experimental results of Adams and Miller 26 and Singh et al 27 In this paper, we report the densities of the NH x radicals in a remote Ar-NH 3 -SiH 4 plasma and we focus on the role of these radicals in the deposition process of silicon nitride. In Sec.…”
Section: Introductionmentioning
confidence: 99%